Agenda for the Evolution of Canonical Administrative Justice - Montini, Gianpaolo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
In the context of the theme of the challenges awaiting the law of the Church forty years after the promulgation of the current Code, the article proposes to foresee the desired evolution of canonical administrative justice, sharing the responsibilities of the agenda among the various subjects of the mission of the Church, starting from the faithful up to the supreme and universal legislator. The evolution of the administrative justice system — perhaps like every other area of law — cannot be carried on the shoulders of the legislator alone, but is a choral work: by the faithful who must develop a greater awareness of their rights to participate in the mission of the Church, to the lawyers who must operate with greater competence and courage, to the Dicasteries of the Roman Curia who must more proceduralise hierarchical recourses, to the diocesan Bishops who must develop more effective regulations for conciliation regulation. The article sets out in particular some proposals for an evolution of the jurisprudence of the Supreme Tribunal of the Apostolic Signatura and the proposal that the supreme and universal legislator allows the establishment of local administrative courts at the request of individual Bishop’s Conferences.
Keywords: administrative justice; hierarchical recourses; local administrative tribunals